The Role of BNCT in Breast Cancer Treatment - B. Poedjomartono; Y. Sardjono; E. Meiyanto; H. Winarno (Atom Indonesia, 2019)
Boron neutron capture therapy (BNCT) is a promising future technique of breast cancer therapy. BNCT is a cell-targetting therapy. In BNCT, the use of boron-10 combined with curcumin analog will provide selective radiation therapy only to breast cancer cells, whereas healthy cells will not be affected. This is because the alpha radiation from the boron-10 nuclei that fission due to thermal neutron irradiation only has a short range of between 4 and 9 μm, whereas the cell diameter is between 10and 20 μm, so the reaction is limited only to the cancer cells. If the development of BNCT succeeds, then in the future the malignancy of the breast cancer will be effectively treated by cancer-cell targeted therapy, thereby avoiding the side effects of conventional therapy.